1992
DOI: 10.1017/s002221510011895x
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of pseudocyst of the auricle

Abstract: Four male patients with pseudocyst of the auricle were successfully treated with oral corticosteroids. This condition is an asymptomatic, non-inflammatory, cystic swelling, usually located in the scaphoid or triangular fossa of the anti-helix which if untreated, leads to deformity of the pinna. All successful methods of treatment described in the literature so far have been invasive. All four patients in the above series responded to oral steroid therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“… 7 However, Job et al reported good results by treating 4 patients with oral corticosteroids. 8 Unfortunately, patients involved in both series were small and it would be difficult to interpret the significance of their findings.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, Job et al reported good results by treating 4 patients with oral corticosteroids. 8 Unfortunately, patients involved in both series were small and it would be difficult to interpret the significance of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…The role of steroids in treatment is controversial. Medical management of pseudocysts using systemic steroids was successful in a study by Job 14 but unsuccessful in another by Glamb. 15 Intra-lesional injections of steroids has been reported by Hideaki 16 to have limited success, with most patients requiring more than one injection and having at least one recurrence.…”
Section: 13mentioning
confidence: 99%
“…[10] Incisional drainage or needle aspiration followed by compressive dressing is also one of the most commonly practised methods, but this is associated with a recurrence rate of about 38%. [11] Job and Raman [12] and Miyamoto et al, [13] successfully applied aspiration followed by intracystic injection of steroids to treat their patients. Recurrent auricular pseudocysts have also been eff ectively treated by several authors with aspiration and oral/ intralesional steroid administration.…”
Section: Discussionmentioning
confidence: 99%